Synthesis and Medicinal Properties of 4-Benzylidene-1-phenyl-2-(substituted styryl)imidazolin-5-ones - Madhavi, K.; Prasad, K.V.S.R.G.; Bharathi, K. (Asian Journal of Chemistry, 2010)
A series of 4-benzylidene-1-phenyl-2-(substituted styryl)imidazolin-5-ones have been synthesized by the interaction of 4-benzylidene-2-methyloxazol-5-one with different Schiff bases, prepared by simple condensation of aniline and various substituted benzaldehydes. The title compounds were evaluated for antiinflammatory activity in carrageenan foot paw edema model and in vitro antioxidant activity. Among the 14 compounds synthesized, dimethyl amino derivative and sterically hindered phenolic derivatives were found to possess good antiinflammatory activity which also exhibited antioxidant properties.